Análise da influência dos fenômenos el niño e la niña na ocorrência de eventos climáticos de seca e enchente - Bragança, Cassiano Gustavo Juan Franco Neves (2024)
The effects of climate change are increasingly evident, with the incidence of drought and flood events being noticeable throughout the national territory and in the rest of the world resulting from changes in atmospheric systems. Among the factors that can influence hydrological and meteorological parameters in certain regions, it is worth highlighting the occurrence of the El Niño and La Niña phenomena, recurrently correlated with drought and flood events. Therefore, the main objective of the present work is to analyze the influence of El Niño and La Niña on drought and flood events recorded in Brazil. Historical series of precipitation and flow recorded between the years 1940 and 2018 were analyzed, covering stations installed and in operation in Espírito Santo, Minas Gerais, Rio Grande do Sul, Bahia and Ceará. Then, the data were classified according to the incidence and intensity of the phenomena. The average annual precipitation totals from the historical series and during the El Niño and La Niña years were spatialized using the Inverse Distance Weighted (IDW) interpolation method in the QGIS 3.28.8 computational application. Furthermore, the averages obtained with data referring to the period of water crisis that occurred in Espírito Santo between the years 2014 and 2016 were analyzed and compared, discussing the effects of El Niño and La Niña on the records of stations located in Espírito Santo Santo and verifying the variations in the Oceanic Niño Index – ONI in different periods. After preparing the results, historical precipitation and flow data were acquired from other periods within the interval between 1940 and 2018, considering the need to contemplate the greater number of El Niño and La Niña phenomena in other regions of the national territory. Data obtained from stations in Espírito Santo showed a reduction in average precipitation in years of strong El Niño in most stations in the state, with the inverse relationship occurring in periods of strong La Ninã, increasing precipitation and flow values. Interpolation using the IDW method showed a reduction in precipitation in the North of Espírito Santo in El Niño years and an increase in rainfall in the South region. Stations located in Rio Grande do Sul recorded an increase in average precipitation and flow during El Niño years. El Niño and the reduction in La Niña years. The stations of Minas Gerais, Bahia and Ceará presented variations in the analyzes considering the years of El Niño and La Niña; however, the values obtained were not very significant in indicating the influence of the phenomena, and it is prudent to consider the interference of other factors that may affect the hydrological variables analyzed. When analyzing the period of water crisis in Espírito Santo, it was found that the greater intensity of El Niño may be related to drought events in Espírito Santo, presenting a reduction in the average rainfall records in more intense El Niño years according to with ONI.